Effect of the rotor crank system on cycling performance - Jobson, S. A.; Hopker, J.; Galbraith, A.; Coleman, D. A.; Nevill, A. M. (Journal of Sports Science & Medicine, 2009)
The aim of this study was to evaluate the impact of a novel crank system on laboratory time-trial cycling performance. The Rotor system makes each pedal independent from the other so that the cranks are no longer fixed at 180°. Twelve male competitive but non-elite cyclists (mean ± s: 35 ± 7 yr, Wmax = 363 ± 38 W, VO2peak = 4.5 ± 0.3 L·min-1) completed 6-weeks of their normal training using either a conventional (CON) or the novel Rotor (ROT) pedal system. All participants then completed two 40.23-km time-trials on an air-braked ergometer, one using CON and one using ROT. Mean performance speeds were not different between trials (CON = 41.7 km·h-1 vs. ROT = 41.6 km·h-1, P > 0.05). Indeed, the pedal system used during the time-trials had no impact on any of the measured variables (power output, cadence, heart rate, VO2, RER, gross efficiency). Furthermore, the ANOVA identified no significant interaction effect between main effects (Time-trial crank system*Training crank system, P > 0.05). To the authors' knowledge, this is the first study to examine the effects of the Rotor system on endurance performance rather than endurance capacity. These results suggest that the Rotor system has no measurable impact on time-trial performance. However, further studies should examine the importance of the Rotor 'regulation point' and the suggestion that the Rotor system has acute ergogenic effects if used infrequently.